PENGARUH CONTINUITY OF CARE TERHADAP KETIDAKNYAMANAN DALAM KEHAMILAN DI PRAKTIK MANDIRI BIDAN NURACHMI SST. M.Kes KOTA PALEMBANG 2023 - Eka Rahmawati; Arie Anggraini; Reffi Dhamayanti; Ahmad Arif (Jurnal Cakrawala Ilmiah, 2023)
Continuous care is carried out with the aim of providing comprehensive services that can be started from the preconception period, early pregnancy, during pregnancy in each trimester, labor process, BBL care, to postpartum. This study is to analyze the effect of Continuity Of Care on the health of pregnant women, maternity mothers, postpartum mothers, and neonates. Method: This study used a quasi-experimental design with the Posstest-Only Control Design method. In this design, the samples were divided into two groups, namely, group I carried out continuous assistance and group II as a control. Data sources in this study used primary data in the form of observation sheets and secondary data from medical records, MCH books, and registers. The number of samples in this study was 100 respondents, which were divided into 2 groups with each group of 50 respondents. Statistical tests used Mann Whitney test. Results: There was a significant difference between pregnancy discomfort. Statistically obtained a p value of 0.030; P<0.05. Conclusion: Pregnant women who are given continuous care have different discomfort experienced compared to those who are not given continuous care.